Integration of Medical Physical Principles with Empathy as Scientific Strengthening and Counseling Action - Indreswari, Henny; Utami, Nugraheni Warih; Prihatiningsih, Riskiyana; Apriani, Rizka (Department of Guidance and Counseling, FIP, Undiksha, 2021)
This study aims to see a picture of empathy by integrating biological, sociological and psychological by using a delayed broadcast application which is intended to help Guidance and Counseling students to increase empathy and communication skills through a biopsychosocial approach to identify counselee problems. The implementation study uses a formative evaluation framework to see the counselor's communication with the counselee through three stages; 1) evaluation, consisting of a conceptual review; 2) technical, both formal and informal by the lecturer; 3) evaluation of Guidance and Counseling students who are involved in surveys and observations. The findings of this study indicate that bio-psycho-social video delays can improve counseling communication techniques (empathy) for prospective counselors. The results of this study can be used as a reference for lecturers and prospective counselors in providing learning about the counseling process so as to improve the quality of prospective counselors, especially in increasing empathy which is one of the counselor's character competencies.